2004
DOI: 10.1088/0305-4470/37/49/001
|View full text |Cite
|
Sign up to set email alerts
|

Metric features of a dipolar model

Abstract: The lattice spin model, with nearest neighbor ferromagnetic exchange and long range dipolar interaction, is studied by the method of time series for observables based on cluster configurations and associated partitions, such as Shannon entropy, Hamming and Rohlin distances. Previous results based on the two peaks shape of the specific heat, suggested the existence of two possible transitions. By the analysis of the Shannon entropy we are able to prove that the first one is a true phase transition corresponding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…[13,14,15,16]. For applications in the spirit of our demands, see also [11,12,17,18]. Here we only recall the definitions of Shannon entropy and Rohlin distance.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14,15,16]. For applications in the spirit of our demands, see also [11,12,17,18]. Here we only recall the definitions of Shannon entropy and Rohlin distance.…”
Section: Discussionmentioning
confidence: 99%
“…Analytical and Monte Carlo (MC) calculations have shown the following picture: For a fixed coupling δ > 0.4403, the phase diagram initially exhibits the alternating striped spin configurations as described above, characterizing the so called smectic striped phase. As the temperature increases, the initial picture describes a transition into the tetragonal phase [10,11,12,13] characterized by states with orientationally disordered stripes but still preserving some of this structural form, which tends to the completely disordered paramagnetic state. Recent numerical results related to this striped-tetragonal phase transition indicate a continuous transition for h = 1 [14], a clear first-order transition for h = 2 [11,14], a likely weaker first-order transition for h = 3 [14], and a continuous transition for h = 4 [14] and h = 8 [12].…”
Section: Introductionmentioning
confidence: 99%
“…3,5 In the limit when the stripe width is much larger than the domain walls, the walls can be approximated by Ising walls and the system can be considered as an Ising system of interacting domain walls. 4 In spite of intense theoretical [3][4][5][6][7][8][9][10][11][12][13][14] and experimental 1,2,[15][16][17] work on the behavior of ultrathin magnetic films, the precise nature of the phases and the relaxational dynamics aspects of these systems is still poorly understood. In Monte Carlo simulations of an Ising model on a square lattice, Booth et al 5 found evidence of a stripe phase at low temperatures, with orientational and positional order reminiscent of the smectic order in liquid crystals.…”
Section: Introductionmentioning
confidence: 99%